Climate change and human health: what are the research trends? A scoping review protocol. Issue 12 (23rd December 2016) - Herlihy, Niamh; Bar-Hen, Avner; Verner, Glenn; Fischer, Helen; Sauerborn, Rainer; Depoux, Anneliese; Flahault, Antoine; Schütte, Stefanie
Abstract : Introduction: For 28 years, the Intergovernmental Panel on Climate Change (IPCC) has been assessing the potential risks associated with anthropogenic climate change. Although interest in climate change and health is growing, the implications arising from their interaction remain understudied. Generating a greater understanding of the health impacts of climate change could be key step in inciting some of the changes necessary to decelerate global warming. A long-term and broad overview of the existing scientific literature in the field of climate change and health is currently missing in order to ensure that all priority areas are being adequately addressed. In this paper we outline our methods to conduct a scoping review of the published peer-reviewed literature on climate change and health between 1990 and 2015. Methods and analysis: A detailed search strategy will be used to search the PubMed and Web of Science databases. Specific inclusion and exclusion criteria will be applied in order to capture the most relevant literature in the time frame chosen. Data will be extracted, categorised and coded to allow for statistical analysis of the results. Ethics and dissemination: No ethical approval was required for this study. A searchable database of climate change and health publications will be developed and a manuscript will be complied for publication and dissemination of the findings. We anticipate that this study will allow us to map the trends observed in publications over the 25-year time period in climate change and health research. It will also identify the research areas with the highest volume of publications as well as highlight the research trends in climate change and health.